A Quality-of-Life Comparison of Two Fecal Incontinence Phenotypes: Isolated Fecal Incontinence Versus Concurrent Fecal Incontinence With Constipation. Issue 1 (January 2019) - Cauley, Christy E.; Savitt, Lieba R.; Weinstein, Milena; Wakamatsu, May M.; Kunitake, Hiroko; Ricciardi, Rocco; Staller, Kyle; Bordeianou, Liliana
Abstract : BACKGROUND: Many patients with fecal incontinence report coexisting constipation. This subset of patients has not been well characterized or understood. OBJECTIVE: The purpose of this study was to report the frequency of fecal incontinence with concurrent constipation and to compare quality-of-life outcomes of patients with fecal incontinence with and without constipation. DESIGN: This was a prospective cohort study. Survey data, including Fecal Incontinence Severity Index, Constipation Severity Instrument, Fecal Incontinence Quality of Life survey (categorized as lifestyle, coping, depression, and embarrassment), Pelvic Organ Prolapse Inventory and Urinary Distress Inventory surveys, and anorectal physiology testing were obtained. SETTINGS: The study was conducted as a single-institution study from January 2007 to January 2017. PATIENTS: Study patients had fecal incontinence presented to a tertiary pelvic floor center. MAIN OUTCOME MEASURES: Quality-of-life survey findings were measured. RESULTS: A total of 946 patients with fecal incontinence were identified, and 656 (69.3%) had coexisting constipation. Patients with fecal incontinence with constipation were less likely to report a history of pregnancy (89.2% vs 91.4%; p = 0.001) or complicated delivery, such as requiring instrumentation (9.1% vs 18.1%; p = 0.005), when compared with patients with isolated fecal incontinence. Patients with fecal incontinence with constipation had higher rates of coexisting pelvic organ prolapse (Pelvic Organ Prolapse Inventory: 18.4 vs 8.2; p < 0.01), higher rates of urinary incontinence (Urinary Distress Inventory: 30.2 vs 23.4; p = 0.01), and higher pressure findings on manometry; intussusception on defecography was common. Patients with fecal incontinence with concurrent constipation had less severe incontinence scores at presentation (21.0 vs 23.8; p < 0.001) and yet lower overall health satisfaction (28.9% vs 42.5%; p < 0.001). Quality-of-life scores declined as constipation severity increased for lifestyle, coping, depression, and embarrassment. LIMITATIONS: This was a single-institution study, and surgeon preference could bias population and anorectal physiology testing. CONCLUSIONS: Patients with fecal incontinence with concurrent constipation represent a different disease phenotype and have different clinical and anorectal physiology test findings and worse overall quality of life. Treatment of these patients requires careful consideration of prolapse pathology with coordinated treatment of coexisting disorders. SeeVideo Abstract athttp://links.lww.com/DCR/A783 .